Uso de rituximab en pacientes pediátricos con síndrome nefrótico córtico-resistente. Experiencia de un centro (2015)
ABSTRACT: Steroids are the cornerstone of therapy for nephrotic syndrome (NS) with a remission rate as high as 90%. In patients who do not respond to them or are steroid dependent, other immunosuppressive drugs have been used. Although rituximab use in NS is off-label, many authors have published their experience with it. Objective and methods: To describe retrospectively a group of seven children with nephrotic syndrome, either steroid-dependent (SDNS) or steroid-resistant (SRNS), treated with rituximab and mycophenolate, at Pablo Tobón Uribe Hospital, in Medellín, Colombia. Results: Two patients with SDNS and five with SRNS were evaluated; median age at diagnosis was 2 years (p25-75: 1-5); six months after treatment with rituximab there was reduction in proteinuria (93%), in the steroid dose (100%) and in the relapse episodes. However, proteinuria reappeared 12 months after treatment. Conclusion: During the first year after rituximab treatment of NS there is reduction in proteinuria and in the steroid dose, but thereafter there is relapse. It is suggested to carry out another study using a second dose of rituximab one year after the first one.